Porta Hepatic Schwannoma on FDG PET/CT - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Schwannomas are benign tumors that arise from Schwann cells of neural sheath. They can occur in any part of the body. However, the most common locations are the head, neck, spinal cord, and extremities. Schwannoma in the porta hepatis is extremely rare. Herein, we describe a case of porta hepatic schwannoma in a 36-year-old woman who presented with abdominal pain for a month.
Keywords: FDG PET/CT; porta hepatis; schwannoma